The Effectiveness of Kumon Learning Method Toward Student’s Reading Comprehension Skill: English - Diska Virgiyanti; Alianda Luthfan Dzaki; Aries Fachriza; Annisa Kurnia Asri (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
English proficiency has become increasingly important in supporting students’ academic and future professional success, encouraging parents to seek additional English learning opportunities outside formal education. One of the widely adopted institutions is Kumon, which applies an individualized and self-paced learning approach. However, studies discussing the effectiveness of the method in Kumon course in improving reading comprehension skills in English as a Foreign Language (EFL) classes remain limited, particularly in the Indonesian students. Therefore, this study aims to examine the effectiveness of the Kumon Learning Method toward students’ reading comprehension skills at Kumon course that is located in Ahmad Yani street, Purwokerto, East Java, Indonesia. This research employed a descriptive qualitative design involving six students aged 11–12 years old enrolled in the EFL Class. Data were collected through interviews, observations, questionnaires, and documentation. The findings reveal that the Kumon Learning Method effectively enhances students’ reading comprehension through individualized learning, leveled worksheets, repetitive practice, and Oral Reading Check (ORC) activities. Students demonstrated improvements in vocabulary acquisition, reading fluency, comprehension ability, confidence, and learning independence. In conclusion, the Kumon Learning Method provides an effective supplementary approach for improving reading comprehension skills in EFL learning and may serve as an alternative model for supporting English language development among young learners.